Vision, future, cycle and effect: A community life course approach to prevent prenatal alcohol exposure in central Australia. (24th November 2021) - Lemon, Donna; Swan‐Castine, Justine; Connor, Elizabeth; van Dooren, Fleur; Pauli, Jenna; Boffa, John; Fitzpatrick, James; Pedruzzi, Rebecca Anne
Abstract: Issue addressed: Prevention approaches specific to prenatal alcohol exposure (PAE) and foetal alcohol spectrum disorder (FASD) have been identified as urgently needed in Australia, including in Aboriginal and Torres Strait Islander communities. However, very little work has aimed to describe and evaluate health promotion initiatives, especially those developed in rural and remote areas. Methods: A series of television commercial scripts (scripts) were developed with health promotion staff at an aboriginal and Torres Strait Islander Community Controlled Health Service and piloted with 35 community members across six yarning sessions. Results: Scripts evoked responses in line with two predominant themes: "Strength" and "Community resonance." This process led to the development of a four‐part television and radio campaign focusing on a life course approach to prevent prenatal alcohol exposure (PAE) – "Vision, " "Future, " "Cycle" and "Effect." Conclusions: Intergenerational influences on PAE were key elements of scripts positively received by community members. Strengths of this work included a flexible approach to development, local aboriginal men and women coordinating the yarning sessions, and the use of local actors and familiar settings. So what?: Preventing PAE is extraordinarily complex. Initiatives that are culturally responsive and focus on collective responsibility and community action may be crucial to shifting prominent alcohol norms. Future work is necessary to determine the impact of this campaign.